Efisiensi Usaha Peternakan Ayam Broiler dengan Sistem Manajemen Closed House dan Open House - Yanita Mutiaraning Viastika (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2021)
This study aims to identify the ratio of broiler farm business income with closed house and open house management systems. The research method used was a survey method using purposive sampling. As treatment there are two cage management systems, namely closed house and open house. The research method uses profit analysis and R / C ratio. The results showed that 1) the profit obtained by the broiler breeder business with the open house cage system was greater than that of the closed house. 2) the broiler chicken coop business that uses the open house and closed house systems is classified as efficient. This finding implies that chicken farmers can choose an open house cage system because it is more profitable.